PREFIKS PEMBENTUK VERBA BAHASA TAA - Nismawati, Nismawati (BAHASA DAN SASTRA, 2013)
This research intent to describe the meaning and form of prefix verb of Taa language in Molowagu village. This research is qualitative research that passed through several phase, which is data collection, analysis data and data presentation. The method that used in collecting the data are listening and speaking with the inducement and record techniques. In analyzing the data the researcher used equal and distribution method. Then, in presentation the data, She used formal and informal method. The results of this research illustrated that:Â  First, prefix verb of Taa language are {muN-}, {mu-}, {maN-}, {dar-}, {ni-}, {ti-}, {ri-}, { pu-}, {pak-}, dan {pap-}. Prefix {muN-} has three allomorphs, they are {mun-}, {mung}, dan {muny} with the appropriate context. Second, the prefix has meaning that explain action or doing something with the suitableÂ  form and meaning that have related with the time.